Apcietinājuma piemērošanas problemātika un tendences Rīgas tiesas apgabala prokuratūrā - Trušels, Māris (Latvijas Universitāte, 2007)
Diplomdarba nosaukums ir “Apcietinājuma piemērošanas problemātika un tendences Rīgas tiesas apgabala prokuratūrā”. Diplomdarba mērķis ir ar likuma, prakses materiālu un starptautiskās prakses analīzes palīdzību atklāt tās apcietinājuma piemērošanas tendences un problemātiku, kas ir vērojamas Rīgas tiesas apgabala prokuratūrā. Diplomdarba ievadā tiek pamatots temata svarīgums un tā aktualitāte, kā arī noteikti darbā nospraustie mērķi un līdzekļi to sasniegšanai. Pirmajā diplomdarba nodaļā ir apskatīti apcietinājuma piemērošanas vispārīgie nosacījumi, kas ir paredzēti Kriminālprocesa likumā, apskatīta Rīgas tiesas apgabala prakse šajā jautājumā. Otrajā nodaļā ir apskatīta cilvēktiesību garantēšana jautājumos par apcietinājuma piemērošanu, analizēti izmeklēšanas tiesneša institūta svarīgākie aspekti. Diplomdarba trešā nodaļa vēsta par starptautisko praksi, pieredzi jautājumos par apcietinājuma piemērošanu un tās attiecināmību uz Rīgas tiesas apgabala prokuratūras praksi Diplomdarba izstrādē ir izmantoti 19 avoti.

The name of diploma paper is „Problems and tendencies of application of arrest in Riga Court District Prosecutor’s Office”. The aim of this diploma paper is to reveal the problems and tendencies of application of arrest observed in Riga Court District Prosecutor’s Office with the help of the law, practice materials and the analysis of international practice. In introduction the importance of the current theme and its urgency is observed, as well as the targets and means of achievement are defined. In the first chapter of the work describes the common conditions of application of arrest, provided by the law of criminal procedure, as well as the practice of Riga Court District Prosecutor’s Office in this question. The second chapter deals with the guarantee of human rights in cases connected with application of arrest. The main aspects of the institute of investigation judge are analyzed. The third chapter deals with international practice and experience in the cases of the application of arrest and their attribution to the practice of Riga Court District Prosecutor’s Office. In conclusion the results of the research and analysis of the works are summed up, as well as completed tasks are described. The bibliography list contains 19 resources attached at the end of the work.
Problematic and tendency of the arrest accommodation in Riga court district prosecutor's office
Keywords: Tiesības